Natural Products Modulate Cell Apoptosis: A Promising Way for the Treatment of Ulcerative Colitis - Liu, Chenhao; Zeng, Yiwei; Wen, Yulong; Huang, Xinggui; Liu, Yi (Frontiers in Pharmacology, 2022)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease with poor outcomes interfering with patients’ quality of life and imposing heavy societal and economic burdens. Apoptosis of intestinal epithelial cells (IECs) is an early event in the onset of UC and plays a crucial role in disease development. Furthermore, it is reported that mediating apoptosis of IECs may result in improved colonic histology and remission of the disease. Thus, targeting apoptosis has been considered a promising therapeutic strategy for UC treatment. In recent years, research on the ameliorative effects of natural products on UC through inhibiting IECs apoptosis has attracted increasing attention and made remarkable achievements ameliorating UC. In this review, we summarized the currently available research about the anti-apoptotic effects of natural products on UC and its mechanisms involving the death-receptor mediated pathway, mitochondrial-dependent pathway, ERS-mediated pathway, MAPK-mediated pathway, NF-κB mediated pathway, P13k/Akt pathway, and JAK/STAT3 and NLRP3/ASC/Caspase-1. We expected this review might highlight the importance of natural products in UC treatment by regulating IECs apoptosis to provide perspectives and ideas for future studies on the prevention and treatment of the disease.